(untitled) (Baghdad Science Journal, 2021)
This study aims to determine the prevalence of Entamoeba histolytica, Entamoeba dispar andEntamoeba moshkovskii by three methods of diagnosis (microscopic examination, cultivation and PCR) thatwere compared to obtain an accurate diagnosis of Entamoeba spp. during amoebiasis. Total (n=150) stoolsamples related to patients were (n = 100) and healthy controls (n= 50). Clinically diagnosed stool samples(n=100) were collected from patients attending the consultant clinics of different hospitals in Basrah duringthe period from January 2018 to January 2019. The results showed that 60% of collected samples werepositive in a direct microscopic examination. All samples were cultivated on different media; the Brain heartinfusion agar showed high efficiency and was the most suitable in cultivating the parasite. Data and results ofmolecular study were indicated by DNA extraction from stool samples and used in PCR technique withspecific primers. This study identifies different infection percentage for the three species. The highestinfection in Basrah patients was Entamoeba moshkovskii 15% followed by Entamoeba dispar 10% andEntamoeba histolytica, which was 5%.